DEVELOPMENT OF THE SYSTEM OF COLLECTION OF PROPERTY TAX FROM INDIVIDUALS - Shamsiyev Nodir Muratovich (Scholar Express Journals, 2022)
This article covers the development of the property tax collection system from individuals. Also, the cases of taking the initiative of property valuation are widely covered. In addition, the ever-changing nature of the property tax market situation is based on the need for tax authorities to use more advanced methods of monitoring the correct calculation of the tax base. In addition, based on the study of the experience of developed foreign countries, two main groups of benefits are distinguished, and conclusions and suggestions on the application of these experiences to property tax are developed.
Keywords: Individuals; property tax; tax base; collection